2019
DOI: 10.3390/jcm8111789
|View full text |Cite
|
Sign up to set email alerts
|

Potential Therapeutic Targets of Quercetin and Its Derivatives: Its Role in the Therapy of Cognitive Impairment

Abstract: Quercetin (QC) is a flavonoid and crucial bioactive compound found in a variety of vegetables and fruits. In preclinical studies, QC has demonstrated broad activity against several diseases and disorders. According to recent investigations, QC is a potential therapeutic candidate for the treatment of nervous system illnesses because of its protective role against oxidative damage and neuroinflammation. QC acts on several molecular signals, including ion channels, neuroreceptors, and inflammatory receptor signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 122 publications
3
25
0
Order By: Relevance
“…Previous animal studies [ 36 , 46 ] highlighted that quercetin and Q3G significantly increased the mRNA expression and secretion of BDNF in rats, which contribute to the neural stem cell proliferation. The possible underlying mechanism could be the quercetin activates BDNF-TrkB and its associated signaling pathway, which eventually, results in phosphorylation of CREB, followed by an increase in extracellular signal-regulated kinase (ERK) and BDNF [ 47 , 48 ]. Therefore, quercetin interactions with these pathways may be responsible for its role in the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Previous animal studies [ 36 , 46 ] highlighted that quercetin and Q3G significantly increased the mRNA expression and secretion of BDNF in rats, which contribute to the neural stem cell proliferation. The possible underlying mechanism could be the quercetin activates BDNF-TrkB and its associated signaling pathway, which eventually, results in phosphorylation of CREB, followed by an increase in extracellular signal-regulated kinase (ERK) and BDNF [ 47 , 48 ]. Therefore, quercetin interactions with these pathways may be responsible for its role in the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, quercetin can reverse cognitive impairment and enhance memory in the ageing process. Quercetin has the protective effects of antioxidant damage and neuroinflammation, so it is a potential therapeutic candidate for the treatment of neurological diseases and is helpful for the treatment of cognitive impairment [ 126 , 127 ]. Multiple experiments have shown that quercetin has a neuroprotective effect [ 128 ].…”
Section: Applications Of Quercetinmentioning
confidence: 99%
“…These diseases lead to an irreversible weakening of all brain functions. Around 30 million individuals worldwide are affected by NDDs [3,4]. Alzheimer's disease (AD), vascular dementia (VaD), frontotemporal dementia Figure 1.…”
Section: Introductionmentioning
confidence: 99%